SOCIAL AND RELIGIOUS SEGREGATION IN AMBON CITY - Refo, Ignasius Samson Sudirman; Leiwakabessy, Erly (International Journal of Psychosocial Rehabilitation, 2020)
In the context of sociology, the reality of social and religious segregation explains the relational problems in people's lives. In the conflict in Ambon City, religious segregation has become an instant solution in reducing conflict at the local level. In this sense, physical segregation is carried out, because when identity is strengthened due to violence, conflicting communities will not be easy to trust each other. However, social and religious segregation in Ambon City relatively went well and helped create peace in Ambon City. Through qualitative approach, this research shows the success of Ambon City in overcoming conflict through relocation and social and religious segregation. However, this segregation is not a single solution. The success of segregation is coupled with various community empowerment programs to have multicultural awareness.